2012
DOI: 10.5665/sleep.1700
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Insomnia and Changes in Hypnotics Use in England over 15 Years: Analysis of the 1993, 2000, and 2007 National Psychiatric Morbidity Surveys

Abstract: Insomnia Changes in England Over 15 Years-Calem et al of Finnish populations found evidence of an increase in the reporting of insomnia symptoms over a 10-year period. 4 The authors also found evidence of increased self-reported consumption of hypnotic medication, but not in the prevalence of hypnotic use, implying increased use in people already receiving these agents. An analysis of medication use based on data from the National Psychiatric Morbidity Surveys of 1993 and 2000 found an increase in the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
95
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 15 publications
(15 reference statements)
6
95
1
2
Order By: Relevance
“…Epidemiological studies have demonstrated a higher prevalence of insomnia among the elderly than the younger population as well as a steady increase in the prevalence of insomnia in recent decades (Calem et al, 2012;Ford & Kamerow, 1989;Prinz et al, 1990). Previous studies involving a large elderly population showed that approximately 40% of elderly individuals reported any type of insomnia such as difficulty initiating sleep, difficulty maintaining sleep, early morning awakening, and non-restorative sleep (Calem et al, 2012;Walsh et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Epidemiological studies have demonstrated a higher prevalence of insomnia among the elderly than the younger population as well as a steady increase in the prevalence of insomnia in recent decades (Calem et al, 2012;Ford & Kamerow, 1989;Prinz et al, 1990). Previous studies involving a large elderly population showed that approximately 40% of elderly individuals reported any type of insomnia such as difficulty initiating sleep, difficulty maintaining sleep, early morning awakening, and non-restorative sleep (Calem et al, 2012;Walsh et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…6 Insomnia is common in family physician (FP) settings and is predominantly treated by pharmacotherapy in the United States and elsewhere. [7][8][9][10] Current evidence-based recommendations published by the American Academy of Sleep Medicine and American College of Physicians recommend cognitive behavioral therapy (CBT) as the first-line and most efficacious therapy. 2,11 Despite this, no health system has enough skilled CBT practitioners to treat even a small proportion of insomnia cases.…”
Section: Introductionmentioning
confidence: 99%
“…Women report poorer sleep quality, and they have a 41% increased risk of insomnia compared with men [1][2][3]. Self-reported sleep disturbance in women of reproductive age has been traditionally linked with menstrual cycle phase, and sleep disturbance remains a core symptom of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%